Potensi Biomassa dan Cadangan Karbon pada Tumbuhan Bawah dan Pohon di Hutan Desa Serdang Kawasan Tahura Kabupaten Karo Sumatera Utara - Khairunisa Pratiwi; Melfa Aisyah Hutasuhut; Kartika Manalu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the diversity, biomass potential, and carbon stocks of understory vegetation and trees in the Serdang Village Forest Area of Tahura, Karo Regency, North Sumatra. The methods used were destructive and non-destructive methods with a purposive sampling technique. Sampling was conducted by establishing measurement plots at three observation locations with a transect length of 150 m. Each location consisted of 10 plots, including 5 plots measuring 20 m × 20 m for tree observations and 5 plots measuring 5 m × 5 m for understory vegetation observations. The results showed that 25 understory plant species belonging to 20 families were identified with a diversity index of 2.66, while 22 tree species belonging to 16 families were identified with a diversity index of 2.38. The biomass of understory vegetation was 0.48 tons/ha with an average of 0.136 tons/ha, whereas tree biomass reached 2366.11 tons/ha with an average of 107.55 tons/ha. The carbon stock of understory vegetation and trees was 1183.194 tons/ha with an average of 591.597 tons/ha. Environmental factors influencing the diversity and biomass of understory vegetation and trees included temperature, humidity, light intensity, and altitude. The study concluded that the Serdang Village Forest Area of Tahura, Karo Regency, has a moderate level of biodiversity with high biomass and carbon stock potential, indicating its important role in carbon storage and ecosystem balance. Keywords: Biodiversity, Biomass, Carbon Stock